Reference terms identification of cited articles as topics from citation contexts. (March 2019) - Khalid, Afsheen; Khan, Fakhri Alam; Imran, Muhammad; Alharbi, Mafawez; Khan, Murad; Ahmad, Awais; Jeon, Gwanggil
Abstract: Textual content of citations has been widely applied to access the impact of research outputs, observe knowledge transfer across domains and generate summaries of research articles. These applications, however, experience the problem of correct identification of citational context windows, and alternately use text in a fixed-size window around the citation instance. Citation contexts might contain terms not referenced by the target citation. When application requirement is only the reference terms, this observation ought to be taken into account. This paper tries to find out whether the reference terms of a target citation can be represented as topics derived from its citation contexts or not. We, specifically, consider cases where complete statements are referred to by a citation and cases where there are no explicit reference terms. Evaluation results show that in a majority of cases, reference terms of a citation can be replaced with topics generated from its contexts.